Specific uptake of radioiodinated fragment E1 by venous thrombi in pigs. - L C Knight; S A Olexa; L S Malmud; A Z Budzynski (The Journal of Clinical Investigation, 1983)
Fragment E1, a product of plasmic digestion of cross-linked fibrin, binds specifically in vitro to polymerized fibrin but not to fibrinogen. Purified human Fragment E1 was radiolabeled with 125I or 131I by the Iodogen technique. The uptake of radioiodinated Fragment E1 in vitro into forming or preformed clots was demonstrated. Animal biodistribution studies of radioiodinated Fragment E1 showed its rapid removal from the circulation; radioactive catabolites did not reside long in any organ and were excreted in the urine. The uptake in vivo was evaluated in pigs with preexisting venous thrombi of various ages from 1 h up to 5 d at the time of intravenous systemic injection of the tracer. Radioiodinated fibrinogen was also injected into the same animals to compare the uptake of the two tracers. Thrombus-to-blood ratios for Fragment E1 averaged 43:1 (range 10-108) and 29:1 (range 8-107) in thrombi 1-6 h and 1-5 d old, respectively. In contrast, mean thrombus-to-blood ratios for fibrinogen were, in the same time intervals, 26:1 (range 17-41) and 2:1 (range 0.5-3.9), respectively. It is concluded that radioiodinated Fragment E1 is a specific marker of thrombi in vivo: its uptake by fresh thrombi is better than that of labeled fibrinogen and, in contrast to radioiodinated fibrinogen, this fragment is incorporated into old thrombi as well.